Generation of human iPSCs from urine derived cells of a patient with a novel homozygous PAI-1 mutation - Afzal, Muhammad Zeeshan; Gartz, Melanie; Klyachko, Ekaterina A.; Khan, Sadiya Sana; Shah, Sanjiv J.; Gupta, Sweta; Shapiro, Amy D.; Vaughan, Douglas E.; Strande, Jennifer L. (Stem cell research, 2016)
We have generated a human induced pluripotent stem cell (iPSC) line under feeder-free culture conditions using the urine derived cells (UCs) collected from subject with a novel homozygous Plasminogen Activator Inhibitor-1 (PAI-1 null) mutation. The Sendai virus (SeV) vector encoding pluripotent Yamanaka transcription factors was used at a low multiplicity of infection to reprogram the PAI-1 UCs.